Комплексний аналіз аварійних ситуацій генеруючого обладнання електростанцій - Федоренко, Г.М.; Кенсицький, О.Г. (Технічна електродинаміка, 2012)
Basic principles of analysis of emergency situations of generating equipment of power-stations are considered. Examples of analysis of accidents of powerful turbine generators of power units of NPP are made. Measures are offered on the improvement of the checking and monitoring systems of equipment and operating normatively-technical documentation.